2011
DOI: 10.4315/0362-028x.jfp-10-458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Poisson Distribution-Based Approach for Testing Boundaries of Real-Time PCR Assays for Food Pathogen Quantification

Abstract: The validation of quantitative real-time PCR systems and above all, proof of the detection limit of this method, is a frequently and intensively discussed topic in food pathogen detection. Among proper sample collection, assay design, careful experimental design, execution of real-time PCR, and data analysis, the validation of the method per se ensuring reliable quantification data is of prime importance. The purpose of this study was to evaluate a novel validation tool for real-time PCR assays, based on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…The Cp and standard deviations for the 1 copy dilutions were 41.0 ± 0.8 for the 18S rRNA assay and 37.1 ± 0.9 for the hsp70 assay. For all qPCR assays the percentage of positive reactions for the 1 copy dilution followed the Poisson distribution expected for low copy number solutions (Bustin et al, 2009;Rossmanith and Wagner, 2011) demonstrating reliable amplification of a single copy of target DNA under ideal conditions. It was necessary to identify a Cp value cut-off or boundary where samples with a Cp value above would be considered unreliable or negative.…”
Section: Real-time Quantitative Pcr Amplificationmentioning
confidence: 99%
“…The Cp and standard deviations for the 1 copy dilutions were 41.0 ± 0.8 for the 18S rRNA assay and 37.1 ± 0.9 for the hsp70 assay. For all qPCR assays the percentage of positive reactions for the 1 copy dilution followed the Poisson distribution expected for low copy number solutions (Bustin et al, 2009;Rossmanith and Wagner, 2011) demonstrating reliable amplification of a single copy of target DNA under ideal conditions. It was necessary to identify a Cp value cut-off or boundary where samples with a Cp value above would be considered unreliable or negative.…”
Section: Real-time Quantitative Pcr Amplificationmentioning
confidence: 99%
“…Swabbing was omitted in this setup, but three time periods were included. Since it was demonstrated that the prfA assay can detect and quantify even down to a single molecule (17), each positive signal in qPCR was rated as a positive result. The results summarized in Tables 2 and 3 show that stickers detected both bacterial species repeatedly from several locations, suggesting suitability as an appropriate on-site sampling/detection system.…”
Section: Resultsmentioning
confidence: 99%
“…A promising departure from growth-based methods is quantitative PCR (qPCR), which provides faster results. Theoretically, the detection limit of this method approaches one copy of the target gene (17). Practically, it is an especially sensitive tool that has undergone enormous developmental progress over the past several years (18).…”
mentioning
confidence: 99%
“…The technique is capable of detecting a single DNA copy . And as the number of positive reactions follows the Poisson distribution , and each copy is counted in the Poisson distribution, this implies directly that each copy will be amplified in the real detection system.…”
Section: Discussionmentioning
confidence: 99%